Exploring the role of curriculum materials in teacher professional development. Issue 2 (27th May 2021) - Moore, Nick; Coldwell, Mike; Perry, Emily
ABSTRACT: Curriculum materials (schemes of work, lesson plans, etc.) play a complex and pivotal role in school and teacher practices. The adaptation and development of curriculum materials often constitute part of teacher professional development (PD) activities. However, compared with research examining the relationship between PD and teacher professional change, the role of curriculum materials in professional learning remains under-researched and under-theorised. We address this gap by applying a multi-perspectival approach to data from a PD programme in which teachers were supported to develop curriculum materials. We use an interconnected model to analyse the role of curriculum materials in catalysing change in individual teachers' practice. Our use of Boundary Theory proposes that curriculum material adoption is mediated by the solidity of boundaries between school practice and research findings, and Actor-Network Theory perspectives examine the assemblage of networked relations within and beyond schools that are entangled in curriculum materials. We highlight how combining linear and non-linear perspectives may contribute to improved understanding of the complexity of supporting teachers' learning and use our analyses to outline implications of using curriculum materials in teacher professional development.